Effect of Elevated Salt Concentrations on the Aerobic Granular Sludge Process: Linking Microbial Activity with Microbial Community Structure - Bassin, J. P. (American Society for Microbiology, 2011)
The long- and short-term effects of salt on biological nitrogen and phosphorus removal processes were studied in an aerobic granular sludge reactor. The microbial community structure was investigated by PCR-denaturing gradient gel electrophoresis (DGGE) on 16S rRNA and amoA genes. PCR products obtained from genomic DNA and from rRNA after reverse transcription were compared to determine the presence of bacteria as well as the metabolically active fraction of bacteria. Fluorescence in situ hybridization (FISH) was used to validate the PCR-based results and to quantify the dominant bacterial populations. The results demonstrated that ammonium removal efficiency was not affected by salt concentrations up to 33 g/liter NaCl. Conversely, a high accumulation of nitrite was observed above 22 g/liter NaCl, which coincided with the disappearance of Nitrospira sp. Phosphorus removal was severely affected by gradual salt increase. No P release or uptake was observed at steady-state operation at 33 g/liter NaCl, exactly when the polyphosphate-accumulating organisms (PAOs), “Candidatus Accumulibacter phosphatis” bacteria, were no longer detected by PCR-DGGE or FISH. Batch experiments confirmed that P removal still could occur at 30 g/liter NaCl, but the long exposure of the biomass to this salinity level was detrimental for PAOs, which were outcompeted by glycogen-accumulating organisms (GAOs) in the bioreactor. GAOs became the dominant microorganisms at increasing salt concentrations, especially at 33 g/liter NaCl. In the comparative analysis of the diversity (DNA-derived pattern) and the activity (cDNA-derived pattern) of the microbial population, the highly metabolically active microorganisms were observed to be those related to ammonia (Nitrosomonas sp.) and phosphate removal (“Candidatus Accumulibacter”).